PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MERONCE SISWA KELAS V SDN 72 PEKANBARU - Dian Apriliyana; Zariul Antosa; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study was motivated by the low skills of students in meronce, the average value of 69.9 and was lower than the minimum completeness criteria specified namely 70. The number of students 28 people, students who completed only 12 students with a percentage of 42.9 %, while students who did not complete 16 students with a percentage of 57.1 %. In addition, the lack of creativity in learning meronce activity, because the teacher does not give an idea in advance of a variety of shapes roncean result, only a few people are able to meronce according to the instructions of teachers, because less active teachers guide students in meronce. The hypothesis in this study is a learning model when applied directly, it can increase the skill meronce Elementary School fifth grade students 72 Pekanbaru. This study aims to improve the skills meronce Elementary School fifth grade students 72 Pekanbaru with direct application of learning models with a number of students 28 students. Form of research is classroom action research. The research instrument consisted of learning tools and data collection instruments such as teacher observation sheet activities, student activities, and skills meronce. The data presented in this study are: (1) The skills of students in meronce increase can be seen from the average score of the class is the base class average only 69.9 in the first cycle increases the average grade and cycle menjadi 74,1 II increased to 79.2. This is an increase of 4.2 units from the base score to the first cycle, whereas from the first cycle to the second cycle increased by 5.1 units; (2) Activities of teachers increased from an average of 61.7 % first cycle is increased to 88.3% in cycle II with an increase of 26.7%; and ( 3 ) Student activity during learning with direct instructional model also increased, on average, in the first cycle was 68.3% and the average of the second cycle is 86.7% increased by 18.3%. From the results of the study proved that the application of direct learning model can improve the skills meronce Elementary School fifth grade students 72 Pekanbaru.Keywords: Direct Learning Model, Skills Meronce